AB0389 Evaluation of Serum Level of Golimumab and Antibodies Anti-Golimumab in Patients with Rheumatic Diseases: Results from A Local Registry. (10th June 2014) - Rosas, J.; Llinares-Tello, F.; Martín, S.; Senabre, J.M.; Salas, E.; Oliver, S.; Santos Soler, G.; Santos Ramírez, C.; Barber, X.; Pons, A.; Cano, C.; Lorente, M.
Abstract : Objectives: To assess the clinical relevance of serum levels of Golimumab (GLM) and the prevalence of antibodies anti-Golimumab (anti-GLM-Ab), in patients with rheumatic diseases. Methods: We included 49 test of serum level of GLM and anti-GLM-Ab in 27 consecutives patients, on treatment with GLM at least 6 months, diagnosed of rheumatoid arthritis (RA), peripheral psoriatic arthritis (PsA) (18 test in 9 patients), or ankylosing spondylitis (AS) (31 test in 18 patients). Clinical characteristics, clinical activity index (DAS in 28 joints or SDAI, for RA and PsA; BASFI, BASDAI for AS, were recorded. Serum levels of GLM and anti-GLM-Ab was evaluated by a new ELISA kit developing: Promonitor®-GLM y Promonitor®-anti-GLM-Ab (Proteomika, Derio. Vizcaya. Spain). Cut-off level for serum level of GLM was >32 ng/mL and for anti-GLM-Ab was >20 UA/mL. Serum samples were collected before injection of GLM, and stored frozen -80°C, until analysis. Results: We enrolled 27 patients, 56% were women; mean age 50±12 years. The diagnosis of patients was: RA/PsA in 33% (37% of total test) and AS in 67% (63% of tests). The average time of treatment for the whole population was 14±13 years; but lower in AR/PsA patients respect to AS patients (9.5 vs 17 years; p=0.08). In patients with RA/PsA, the mean DAS28 and SDAI was 2.03±1 and 4.2±5.8 respectively; in AS patients the mean BASDAI and ASDAS was 6.7 and 3.5, respectively. The mean time on treatment with GLM was 12±9 months (range: 1-28). 65% of patients was treated with some DMARD (100% of patients with RA/PsA) and 65% have treated before with some anti-TNF drugs: adalimumab: 40%, etanercept: 35%, infliximab: 25% (1 anti-TNF: 18%; 2 anti-TNF: 31%; 3 anti-TNF: 16%). The mean serum level of GLM was 1.006 ng/mL (RA/PsA: 889 ng/mL vs AS: 986 ng/mL). Three (11%) patients had developed anti-TNF antibodies previously: 2 patients against infliximab and 1 patient against adalimumab. One patient with AS on GLM treatment as the third anti-TNF (adalimumab and etanercept), and with previously ant-adalimumab antibodies, developed anti-GLM-Ab (773 UA/mL), in the sixth month of treatment, losing efficacy (prevalence of anti-GLM-Ab in the total patients: 4%). In the group of patients who had been developed anti-adalimumab antibodies, 20% of them developed anti-GLM-Ab. Conclusions: 1. Immunogenicity induced by GLM is scarce. The prevalence of anti-GLM-Ab was of 4% of patients in this study. 2. In 20% of patients with previous anti-adalimumab antibodies, developed anti-GLM-Ab. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3862